Polyculture of blue tilapia Oreochromis aureus (Steindachner, 1864) and Pacific fat sleeper Dormitator latifrons (Richardson, 1844) in ponds. - Valverde-Moya, José (2024)
Polyculture is a useful strategy for developing sustainable native fish farming. The purpose of this study was to analyze the interactions between juveniles of Oreochromis aureus (blue tilapia) and adults of Dormitator latifrons (Pacific fat sleeper-PFS) in earth ponds and their influence on production and growth. Tilapia with average initial masses of 4.8±4.9 g (1.6-24.4 g) and adult PFS of 86.3±55.0 g (40.2-197.1 g) were used during the experimental phase carried out in 2 ponds divided into 3 sections of 24 m2. Three replicates were used in polyculture composed of 34 juvenile O. aureus and 42 adult D. latifrons individuals per pond at initial densities of 1.42/m2 and 1.75/m2, respectively; in a ratio of 1.0:1.2 tilapia: pocoyo. As a control, only tilapia (4.6±3.5 g) at 1.42/m2 was used in triplicate. A survival of 98% and higher biomass production were found in the monoculture. However, growth rates showed no statistically significant differences between monoculture and polyculture. The polyculture of juveniles of tilapia O. aureus and adults of D. latifrons had a detrimental effect on production performance, demonstrating a negative interaction, with competition for space and food use. Further research is required to choose the densities, combinations, and relative sizes of these species appropriately for the efficient utilization of available resources.